Block erection simulation considering frictional contact with wire ropes. (1st December 2020) - Lee, Hye-Won; Roh, Myung-Il; Ham, Seung-Ho
Abstract: In shipyards, block erection operations are generally conducted by several cranes to transport and vertically rotate blocks. During such operations, potentially risky situations such as interferences between hoisted bodies and crane wire ropes, overloading, and collisions could arise, resulting in major damage. To mitigate the occurrence of these incidents, it is proposed that the interferences between the wire ropes and blocks should be verified in advance to assess the operation plan and prevent structural damage to the blocks. In this study, algorithms that consider the interference between the wire rope and the block were proposed, which consist of contact, sliding, and friction models. A constraint-based wire rope was adopted for the simulation. The contact model detects the interferences and creates or removes the contact nodes at the wire rope. The sliding model subsequently produces the relative motion between the block and the wire rope and updates the position of the contact nodes. Accordingly, the static and kinetic frictional forces were calculated in the friction model. For this application, the block turnover operation was simulated, and the contact forces exerted on the blocks were calculated under various environmental conditions. The results show that the proposed algorithms can be properly applied to block turnover operations. Graphical abstract: Image 1 Highlights: This study proposes an interference algorithm between wire rope and block at block erection. This study suggests the contact model that detects contact and create/remove contact nodes. The sliding model produces relative motion by updating the position of contact nodes. The static and kinetic frictional forces are calculated in the friction model. Interferences are successfully analyzed during block turnover simulation.